Measured acoustic intensities for clinical diagnostic ultrasound transducers and correlation with thermal index. (20th June 2017) - Retz, K.; Kotopoulis, S.; Kiserud, T.; Matre, K.; Eide, G. E.; Sande, R.
ABSTRACT: Objectives: To investigate if the thermal index for bone (TIB) displayed on screen is an adequate predictor for the derated spatial‐peak temporal‐average (ISPTA .3 ) and spatial‐peak pulse‐average (ISPPA .3 ) acoustic intensities in a selection of clinical diagnostic ultrasound machines and transducers. Methods: We calibrated five clinical diagnostic ultrasound scanners and 10 transducers, using two‐dimensional grayscale, color Doppler and pulsed‐wave Doppler, both close to and far from the transducer, with a TIB between 0.1 and 4.0, recording 103 unique measurements. Acoustic measurements were performed in a bespoke three‐axis computer‐controlled scanning tank, using a 200‐ μ m‐diameter calibrated needle hydrophone. Results: There was significant but poor correlation between the acoustic intensities and the on‐screen TIB. At a TIB of 0.1, the ISPTA .3 range was 0.51–50.49 mW/cm 2 and the ISPPA .3 range was 0.01–207.29 W/cm 2 . At a TIB of 1.1, the ISPTA .3 range was 19.02–309.44 mW/cm 2 and the ISPPA .3 range was 3.87–51.89 W/cm 2 . Conclusions: TIB is a poor predictor for ISPTA .3 and ISPPA .3 and for the potential bioeffects of clinical diagnostic ultrasound scanners. Copyright © 2016 ISUOG. Published by John Wiley & Sons Ltd.